Students' Decision to Major In College Is Influenced By Their Interests and Talents - Septiana MS; Miswan Gumanti; Sugiono (Universitas Muhammadiyah Purwokerto, 2023)
Abstract The propensity to select a college major is largely influenced by personal interests and skills. This is so that each person can concentrate on the activities that suit their interests and skills. However, due to a variety of internal and external variables, upper secondary students frequently struggle with the decision of what major to pursue. This will affect how well the major chosen and the person's fundamental interests and abilities mesh. Therefore, further research is required so that students can take this into account while selecting their college major. The outcomes of community service show that a person's interests and skills might affect the college major choice.